The Bride Machine: Duchamp’s Theory of Art Revisited - Ibarlucía, Ricardo (2021)
It is a commonplace in certain areas of art theory and contemporary art practices to consider Marcel Duchamp’s ready-mades as ordinary objects, which have an artistic value that depends more on a theoretical or institutional framework than on an aesthetic experience. The aim of this paper is, on the one hand, to show the his-torical emergence of these artifacts on the light of the impact of the industrial production in avant-garde movements of the early twentieth century. Discussing Walter Benjamin’ s and Jean Brun’s, it argues that Duchamp’s practice has an explanatory prin-ciple, both in the mechanical reproduction of the work of art and in the aestheticiza-tion of the machine. On the other hand, it brings forward some observations regarding Duchamp’s insight on the “total lack of good or bad taste” and the perceptual dimen-sion of a sculptural object as the Large Glass, coming back to Arthur Danto’s inter-pretation of ready-mades and to the notion of “implementation” introduced by Nelson Goodman to define “the process of bringing about the aesthetic functioning that pro-vides the basis for the notion of a work of art”.